Calcineurin inhibitors in the treatment of primary focal segmental glomerulosclerosis: A protocol of systematic review and meta-analysis of randomized controlled trials. Issue 4 (29th January 2021) - Xue, Guozhong; Wang, Xinbin; Li, Shuwen; Dai, Enlai
Abstract: Background: Evidence suggesting a role for including calcineurin inhibitors(CNIs) in early therapy remains limited for low quality and mainly based on small observation cohort study. We will conduct a systematic reviews to explore the effect and adverse effect of calcineurin inhibitors compared with other interventions in the treatment of primary focal segmental glomerulosclerosis (FSGS). Methods: A comprehensive literature search of MEDLINE (through PubMed), EMBASE, The Cochrane Library, Cochrane Central Register of Controlled Trials (CENTRAL) will be conducted. Two investigators will independently select studies, extract data and assess the quality of the included study. Extracted information will include study characteristics, the contents of included randomized controlled trials, outcomes, the quality of randomized controlled trials and etc. A risk of bias tool will be used to assess the methodological quality. Any disagreement will be resolved by the third investigator. There is no requirement of ethical approval and informed consent. Results: This study will provide high-quality evidence for treatment of FSGS in terms of effectiveness and safety. Conclusion: This systematic review aims to provide evidence for treatment of FSGS in different CNIs. Registration: The systematic review and meta-analysis is registered in the OSF REGISTERS (10.17605/OSF.IO/3B7DE) international prospective register of systematic review.